On Freedom : (University of Hawaii Press, 2009)
The various meanings of freedom are difficult to clarify in the discursive language of theory and philosophy. But authors of fiction, poetry, and other narrative forms--using metaphor, parable, and figurative speech--are often at home with what is difficult and too subtle for reason alone. Residing in countries throughout Asia and North America, the authors in On Freedom help us understand the need for cultural, spiritual, and intellectual freedoms in order to have a life that is fully realized.